Crystallization and surface texturing of amorphous-Si induced by UV laser for photovoltaic application - Hong, Lei (2013)
The DPSS Nd:YVO4 UV laser is used to anneal amorphous silicon (a-Si) film to achieve crystallization and nano-dome surface texturing simultaneously in a one-step annealing process. With pulse energy of 380 mJ/cm2 and repetition rate of 20 kHz, the a-Si can be crystallized by the sequential lateral solidification process, which is evidenced by both SEM characterization and Raman spectra. In addition, the nano-dome like structure is confirmed by AFM characterization, which can lead to ∼200% boost in terms of light absorption as measured by UV-Visible - Near-infrared scanning spectrophotometer. This study highlights the great potential of Nd:YVO4 UV laser for its application in thin film Si solar cell industry to improve the film quality and light trapping capability.